Key Factors of Good Aquaculture Pratices (GAP) Management on Shrimp Pond - Riniwati, Harsuko; Atikawati, Dini; Wardana, Fitri Candra; Wike, Wike; Risna, Ita; Ariyanto, Wahyu; Nandini, Sister; Yuslichati, Lailia (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
The shrimp farming industry is a major pillar in the global fisheries economy, its high demand in the international market is a potential for gaining quick profits. However, the use of intensive cultivation technology by large farmers has been suspected in contributing to environmental damage. In light of this, the Ministry of Marine Affairs and Fisheries has implemented a sustainable fisheries development program with the goal of overcoming this negative impact, this includes the implementation of Good Aquaculture Practices (GAP) in accordance with Ministerial Regulation Number: PER.19/MEN/2010 concerning quality control and safety of fishery products. The purpose of this study was to analyze key factors in the application of Good Aquaculture Practices to shrimp farming. This study used a mixed method approach. Data were obtained from shrimp pond experts who joined the East Java shrimp entrepreneur community. The data analysis method used was the Matrix of Cross Impact Multiplication Applied to a Classification (MICMAC) structural analysis. The results showed that 2 variables had been shown to be the most influential and became the main drivers in the application of Good Fish Farming Practices management in shrimp farming, these variables are the "Use of Chemicals, Biological Materials, and Fish Medicines (UCBF)" and "Harvest" (HV).